The Impact of Climate Change on Tennis Performance - a Review of Evidence - Patalong, Mikołaj; Więckowska, Katarzyna; Pustuła, Paweł; Michnowska, Wiktoria; Kołodziej, Przemysław; Czapliński, Mieszko; Szplit, Ewa; Bilyk, Andrii; Bruska, Natalia; Cemaga, Roman (Quality in Sport, 2026)
Background Climate change is one of the defining challenges of the modern era, with growing evidence of its wide-ranging health implications. Increasing attention has been given to its impact on sport, as climatic conditions significantly influence athletic performance and health. Rising temperatures and changing humidity patterns are expected to disproportionately affect outdoor sports such as tennis, increasing health risks for athletes. Aim This study aims to evaluate existing evidence on the impact of climate change on tennis player performance and the functioning of the broader tennis community, providing insights relevant to sports executives, medical professionals and athletes, and supporting the development of adaptation and health-protection strategies. Material and Methods A comprehensive literature review was conducted, analysing 42 studies published between 2000 and 2025 and indexed in PubMed, Google Scholar and Scopus. Results The evidence demonstrates a clear association between climatic conditions, particularly elevated temperatures, and reduced physiological performance, increased risk of adverse health events and impaired recovery. Climate-related disruptions have also affected tournament scheduling. Adaptation measures, such as infrastructure improvements, revised match protocols and targeted education, are increasingly necessary to protect athlete health and strengthen sector resilience. Conclusions Climate change is already impacting the health of athletes and the operational stability of professional tennis. While some adaptation strategies are emerging, more comprehensive action is urgently required to safeguard welfare and ensure long-term sustainability. The global popularity of tennis and the influence of elite athletes could further support advocacy for climate mitigation efforts addressing the root causes of the crisis.